Business To Business In Purchasing MSME Products - Asmita Wulansari Dg. Liwang; Irwan Moridu (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
In the current digital environment, employees are urged to establish social media relationships with clients in order to boost trust and lower the possibility of transactions that can erode client loyalty. The purpose of this study is to evaluate and assess the predisposing factors for customer loyalty, including MSME customers' use of social media, level of trust, and purchase risk. Causal explanatory research is the methodology employed. The research sample consists of small and medium-sized companies that interact with suppliers and use social media for business purposes. A survey was used to gather data, and 212 respondents were given questionnaires. Regression with mediation is instead employed in the data analysis process. The findings indicate that purchase risk is not as effective at moderating the impact of social media use on consumer loyalty as trust is.